Ludicidade e imaginário ... ... suas diversas possibilidades de interlocução para repensar a formação de professores - Bertoldo, Janice Vidal (2004)
This study regards matters that concern the imaginary, the ludicity and the teachers formation, understood as the pillars for education of a social group. We intend to defend the educational value of the ludic in education from a social imaginary perspective and its contribution for a pedagogy of imagination, in order to defend the idea that a ludic methodology could change into a possibility for the learning development in a school environment. We propose to resignify the educational research, in which the imaginary and the symbolic have relevance, since we take into consideration a pedagogic proposal supported on theoretical postulations that explain the conception of human being, education and society. This work aims to contribute to a pedagogical practice which is based on teachers oral report, focused on the teaching memory in the sense of approaching the memory of this professional about his/her school days and childhood, where his/her ludicity takes place. The collaborators of this study are teachers from the public net school in Santa Maria, a city in the state of Rio Grande do Sul. The results show a concern about the conceptual change for the daily practice of games with children in the childhood age. For that purpose, ludic games were put into practice in classes, understood as investigatory resource, education and self-education, enabling the resignificance of teachers trajectories involved in this study, as well as this researcher.